B. A. ROSENFELD AND A. P. YUSHKOVICH'S WORLDVIEW ON OMAR KHAYYAM (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
Omar Khayyam's belief in understanding the world, his emphasis on the role of reason in this process, and his position as a follower of a particular philosophical school are evident. Similar thoughts about Khayyam were also observed, analyzed, and evaluated in the works of Shakespeare, offering a new approach to recognizing the poet’s trends in thinking.